Wskaźniki silnych społeczności jako komponent wskaźników jakości życia - Rogala, Piotr (The indicators of strong communities as a part of quality of life indicators., 2008)
The article presents two sets of indicators used in researching the strength of communities. The Indicators of Strong Communities from Great Britain were the first while the second are the Indicators of Community Strength from Australia. On the basis of presented information and desideration it is stated that these kinds of indicators should be approached as a specific but still very important part of quality of life indicators.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 143-148